Disaster Mitigation Through the Disaster Resilient Village Program in Padang Pariaman District - Fajria, Resti; Putera, Roni Ekha; Kusdarini, Kusdarini (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2024)
The significant vulnerability of Padang Pariaman District to potential tsunamis necessitates extensive mitigation efforts. This study attempts to delineate the steps included in disaster mitigation through the Disaster Resilient Village program as specified in the Regulation of the Head of National Disaster Management Agency (BNPB) Number 1 of 2012. The program seeks to establish self-sufficient nagaris capable of anticipating and mitigating disaster impacts. Implementing both non-structural and structural mitigation measures through this program is a prudent decision to prepare for unforeseen calamities. This study employed a descriptive qualitative approach, collecting data through interviews with 22 local community members and stakeholders as well as field observations. The findings indicate that the disaster resilience program has stagnated and failed to achieve optimal results. This is evident by the lack of substantial progress and monitoring in Katapiang, Seulayat Ulakan, and West Sunua Nagaris, which have been designated as part of the Disaster Resilient Village program in Padang Pariaman District. These findings serve as a reminder for the government and stakeholders to prioritize the implementation of disaster mitigation initiatives, considering the unpredictable nature of disaster timing and intensity.